Preparation method and application of ligusticum chuanxiong hort rhizome extract
The Liaoning Rhizome Extract (RELS) prepared by heating and reflux method with ethanol solution has a significant corrosion inhibition effect on carbon steel in acidic solutions, solving the complex and cost-effective problems of traditional corrosion inhibitor synthesis, and achieving an efficient and environmentally friendly metal corrosion inhibition effect.
Patent Information
- Application Number
- CN202411651988.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-07
AI Technical Summary
In the prior art, the synthesis of traditional organic corrosion inhibitors is complex and costly, pollutes the environment, and the corrosion inhibition effect of carbon steel in acidic solutions is not ideal.
The ethanol solution was heated and refluxed with different concentrations of ethanol, and its effective ingredients were determined by infrared spectroscopy, and used to prepare metal corrosion inhibitors.
As an environmentally friendly corrosion inhibitor, RELS significantly slows down the corrosion of Q235 carbon steel in 0.5 mol/L sulfuric acid solution, with a corrosion inhibition efficiency of 91.7%, and its inhibition of cathode corrosion reaction is more obvious.
Smart Images

Figure CN119571330A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal material protection, and particularly relates to a preparation method and application of a Ligusticum chuanxiong rhizome extract. Background Art
[0002] Carbon steel has excellent machinability, ductility, electrical conductivity and thermal conductivity, and is widely used in various fields. Inorganic acid aqueous solutions play a vital role in industrial production, such as pickling, chemical cleaning, processing, ore production and oil well acidification of steel. However, due to the relatively active chemical properties of steel, it is susceptible to corrosion in an acidic environment. Metal corrosion has a huge impact on economic development. According to statistics, the economic losses caused by corrosion in my country are about 500 billion yuan per year, accounting for about 5% of my country's GDP. Therefore, it is crucial to slow down the corrosion of carbon steel in acidic solutions.
[0003] Studies have shown that adding organic corrosion inhibitors in corrosive environments can effectively slow down metal corrosion. The molecular skeletons of some organic molecules contain heteroatoms (N, O, S, P and other atoms), which can effectively inhibit the corrosion of carbon steel by acidic solutions. The main reason is that iron ions form chelates with heteroatoms, which can form a protective film on the metal surface and slow down metal corrosion. Studies have shown that organic substances such as benzimidazole derivatives and Schiff base molecules have good metal corrosion inhibition properties. However, the traditional synthesis method of organic corrosion inhibitors is complicated, costly, and pollutes the environment. Therefore, it is necessary to find efficient and environmentally friendly organic corrosion inhibitors.
[0004] In recent years, plant extracts have been widely used in the field of metal corrosion protection. Compared with traditional organic corrosion inhibitors, plant extracts as corrosion inhibitors have the advantages of low cost and biodegradability. So far, in acidic media, many plant extracts have obvious corrosion inhibition effects on carbon steel. In 2022, Luo Zhigang and others successfully obtained Acanthopanax senticosus leaf extract by Soxhlet extraction, and conducted in-depth research on the corrosion inhibition performance of the extract on carbon steel in acidic solution. Experimental data show that the corrosion inhibition efficiency of Acanthopanax senticosus leaf extract on carbon steel reaches 97%. In the same year, Lei Ran and others successfully obtained extracts from Sophora japonica seeds by ultrasonic extraction, and studied the corrosion inhibition effect of the extract on aluminum in 1.0 mol / L hydrochloric acid solution by weight loss and electrochemical methods. The results showed that the extract can effectively inhibit the corrosion of aluminum, and the corrosion inhibition efficiency can reach 83.2%. In 2023, Zhou et al.'s study showed that feverfew extract has excellent corrosion inhibition effect on carbon steel in hydrochloric acid medium. Experiments have found that when the concentration of feverfew extract reaches 400 mg / L, the corrosion inhibition efficiency can reach 98.1%. Therefore, the corrosion inhibition effect of plant extracts on carbon steel in acidic solutions is still an important research topic.
[0005] According to the literature, the rhizomes of Ligusticum chuanxiong contain rich organic matter and are used in the fields of medicine, agriculture and chemistry. There are no reports on the research of Ligusticum chuanxiong rhizomes as metal corrosion inhibitors, so we conducted the following research on its metal corrosion inhibition performance. Summary of the invention
[0006] In view of the above-mentioned problems existing in the prior art, the purpose of the present invention is to provide a preparation method and application of a Ligusticum chuanxiong rhizome extract, and the Ligusticum chuanxiong rhizome extract (RELS) is prepared by heating and reflux of ethanol solutions of different concentrations. The effective components of RELS are analyzed by infrared spectroscopy. The results show that the effective components obtained by extracting the Ligusticum chuanxiong rhizome with 75% ethanol solution have a good corrosion inhibition effect on Q235 carbon steel.
[0007] The technical solution adopted by the present invention is:
[0008] First, the present invention provides a method for preparing a Ligusticum chuanxiong rhizome extract, which comprises the following steps:
[0009] Step 1: Crush the rhizomes of Ligusticum chuanxiong and put them into an oven to dry;
[0010] Step 2: adding the dried Ligusticum chuanxiong rhizome powder into a container, and adding an ethanol solution into the container, heating and refluxing for 10 hours, cooling to room temperature, and then filtering under reduced pressure to obtain an extract;
[0011] Step 3: Rotate the extract to evaporate, pour the concentrated extract into a separatory funnel, add an equal amount of petroleum ether, and repeat the extraction;
[0012] Step 4: Place the aqueous phase obtained by extraction in an oven for drying, add distilled water to the dried solid, place it in a centrifuge tube and repeat centrifugation, filter with a needle filter after reduced pressure, place the filtered solution in an oven for drying, and obtain RELS powder.
[0013] In one implementation, in step 1, the rhizome of Ligusticum chuanxiong is crushed into a powder of 500 mesh.
[0014] In some implementations, the volume fraction of the ethanol solution in step 2 is 65%-85%.
[0015] In some implementations, the volume fraction of the ethanol solution in step 2 is 75%.
[0016] In one implementation, the number of extractions in step 3 is 3 times.
[0017] In one implementation, the centrifugation times in step 4 are 3 times, the centrifugation speed is 1000 r / min, and the centrifugation time is 3 min.
[0018] In some implementations, the chemical components of the RELS powder obtained in step 4 include ferulic acid, sucrose and carotene.
[0019] Secondly, the present invention also protects the use of the Ligusticum chuanxiong rhizome extract in the preparation of metal corrosion inhibitors, and the Ligusticum chuanxiong rhizome extract is prepared using the preparation method described above.
[0020] Finally, the present invention also protects a metal corrosion inhibitor, including a rhizome extract of Ligusticum chuanxiong, which is prepared by the above-mentioned preparation method.
[0021] In some embodiments, the concentration of the Ligusticum chuanxiong rhizome extract is 500 mg / L.
[0022] Beneficial effects of the present invention:
[0023] 1. The main components of RELS prepared by the present invention are: ferulic acid, sucrose and carotene; RELS, as an environmentally friendly corrosion inhibitor, significantly slows down the corrosion of Q235 carbon steel under the condition of 0.5 mol / L sulfuric acid solution, and belongs to a mixed corrosion inhibitor, which inhibits the cathode corrosion reaction more significantly. When the temperature is 298K and the concentration is 500 mg / L, the corrosion inhibition effect of RELS is the best, which is 91.7%.
[0024] 2. The adsorption of RELS on the surface of Q235 carbon steel conforms to the Langmuir adsorption isotherm equation and belongs to the adsorption of a monolayer. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 This is the FTIR graph of RELS.
[0027] Figure 2 Nyquist plots (a, b, c) and Bode plots (d, e, f) of Q235 steel samples measured in 0.5 mol / L sulfuric acid solution containing different concentrations of RELS at 298 K, 303 K, and 308 K.
[0028] Figure 3 is the equivalent circuit diagram.
[0029] Figure 4Tafel polarization curves of Q235 steel samples measured in 0.5 mol / L sulfuric acid solutions containing different concentrations of RELS at (a) 298 K, (b) 303 K, and (c) 308 K.
[0030] Figure 5 is the fitting curve of the Langmuir isotherm model; (a) y T =1.108x+0.032, R T 2 =0.998; (b))y T =1.131x+0.038, R T 2 =0.999; (c)y T =1.162x+0.0823, R T 2 =0.985.
[0031] Figure 6 It is the contact angle image of the carbon steel sample surface (a1, a2, a3 correspond to the contact angles without sample at three temperatures, and b1, b2, b3 correspond to the contact angles with sample at three temperatures).
[0032] Figure 7 These are electron scanning microscope images of the carbon steel surface (a1, b1, and c1 correspond to the electron microscope images without sample addition at three temperatures, and a2, b2, and c2 correspond to the electron microscope images with sample addition at three temperatures). DETAILED DESCRIPTION
[0033] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0034] In the following examples, different volume fractions of ethanol solutions were used to extract the rhizomes of Ligusticum chuanxiong, and the optimal volume fraction of the extractant was determined. The main components in the extract were analyzed by Fourier infrared spectroscopy, the corrosion inhibition effect of the extract was analyzed by electrochemical experiments, the hydrophobicity and corrosion inhibition performance of the extract on the carbon steel surface were studied by surface characterization technology, and the adsorption model of the extract on the Q235 carbon steel surface was determined.
[0035] Example
[0036] 1. Experiment
[0037] 1.1 Preparation of Ligusticum chuanxiong rhizome extract
[0038] The rhizome of Ligusticum chuanxiong was crushed into 500 mesh powder and placed in an oven at 70°C until the mass no longer changed. 300g of Ligusticum chuanxiong powder was added evenly to three round-bottom flasks, and 200mL of ethanol solution with a volume fraction of 65%, 75% and 85% was added to the flasks respectively. Heat and reflux for 10h, cool to room temperature and filter under reduced pressure, rotary evaporate the obtained extract, pour the concentrated extract into a separatory funnel, add an equal amount of petroleum ether, and repeat the extraction three times. The obtained aqueous phase was placed in an oven for drying, distilled water was added to the dried solid, and it was placed in a centrifuge tube and centrifuged three times. The speed of the centrifuge was 1000r / min, the centrifugation time was 3min, and the reduced pressure was filtered, and the pore size was 0.45um. Finally, the filtered solution was placed in an oven at 50°C for drying to obtain RELS powder.
[0039] The purity of all Q235 carbon steel samples in the experiment was greater than 99.9%. The Q235 steel electrodes were polished with sandpaper of different specifications (400-2000 mesh), then repeatedly cleaned with pure water and anhydrous ethanol, and finally dried with cold air.
[0040] RELS extracted with 65%, 75% and 85% ethanol solutions were added to 0.5 mol / L sulfuric acid solution to prepare different concentrations of sample solutions. In addition, 0.5 mol / L sulfuric acid solution was used as the blank solution.
[0041] 1.2 Electrochemical experiments
[0042] The electrochemical experiment was carried out using an electrochemical workstation (CHI660E) through a three-electrode system. The three-electrode system consists of a working electrode, a counter electrode, and a reference electrode. The Q235 steel electrode was used as the working electrode (working area was 1 cm×1 cm), the platinum electrode was used as the counter electrode, and the saturated calomel electrode was used as the reference electrode. The treated three electrodes were immersed in the test solution for electrochemical testing. First, the open circuit potential (OCP) was measured, and the time was set to 1200s. Then, the electrochemical impedance spectroscopy (EIS) test was performed, and the test frequency range was 0.01~1×10 5 Hz, the disturbance amplitude is 5mV. Finally, the Tafel test is performed with a scanning range of -750 to -200mV and a scanning rate of 0.1mV / s. The corrosion inhibition efficiency (η) is calculated as follows:
[0043]
[0044] Among them, i corr,0 and i corr represents the corrosion current density of the working electrode in sulfuric acid solution without and with corrosion inhibitor, R ct,0 and R ctRepresent the charge transfer resistance of the working electrode without and with corrosion inhibitor, respectively.
[0045] 1.3 Surface characterization techniques
[0046] Fourier transform infrared spectroscopy (FTIR) was used to test the characteristic functional groups of RELS. Carbon steel samples were immersed in sulfuric acid solution with or without 500 mg / L RELS for 2 hours, washed with pure water and anhydrous ethanol, and then dried with cold air for surface characterization technology testing. The contact angle (CA) was used to test the surface wettability of carbon steel samples. The surface morphology of carbon steel samples was tested using scanning electron microscopy (SEM).
[0047] 2. Results and Discussion
[0048] 2.1 Infrared spectroscopy analysis
[0049] Figure 1 As shown in the figure, FTIR was used to analyze the characteristic functional groups of RELS, among which 3292.34 cm -1 The absorption peak at 2932.34cm is caused by the stretching vibration of the OH bond. -1 The absorption peak at 1626.61cm is caused by the stretching vibration of the CH bond. -1 The absorption peak at 1106.61cm is caused by the stretching vibration of the CC bond and the benzene ring skeleton. -1 and 1000cm -1 The following absorption peaks are caused by the vibration of the C=C bond and the π bond in the benzene ring and the carboxylic acid anion functional group and unsaturated bond. By consulting relevant literature and combining infrared spectrum experimental data, it is inferred that the main chemical components of RELS are ferulic acid, sucrose and carotene, and the molecular structure is shown in the following formula:
[0050] Ferulic Acid:
[0051] sucrose:
[0052] Carotene:
[0053] 2.2 Ethanol solution volume fraction screening
[0054] Under the conditions of 298K and 0.5mol / L sulfuric acid solution, the corrosion inhibition effect of RELS on Q235 carbon steel extracted with 65%, 75% and 85% ethanol solutions is shown in Table 1:
[0055] Table 1 Corrosion inhibition efficiency at different ethanol volume fractions
[0056]
[0057] It can be seen from Table 1 that the extract obtained when the volume fraction of ethanol is 75% has a better corrosion inhibition effect on Q235 steel, and the corrosion inhibition efficiency reaches 86.7%, so the extract when the volume fraction of ethanol is 75% is selected.
[0058] 2.3 Impedance analysis
[0059] Figure 2 The Nyquist and Bode plots of Q235 steel without and with different concentrations of RELS added at different temperatures (298K, 303K, 308K) in a 0.5mol / L sulfuric acid environment. Figure 2 As shown in Figure ac, the impedance spectrum consists of a capacitive arc and an inductive arc. As the concentration of RELS increases, the radius of the capacitive arc shows an increasing trend, which indicates that the number of corrosion inhibitor molecules adsorbed on the surface of the Q235 carbon steel electrode increases, the protective film formed is denser, and the corrosion inhibition effect is better. When the concentration of RELS is 500 mg / L, the RELS corrosion inhibition effect is the best. However, when the concentration is 600 mg / L, the corrosion inhibition efficiency decreases. This is because the number of adsorbed molecules on the surface of the carbon steel electrode is saturated. After exceeding the saturation limit, the adsorbed molecules will rearrange and form gaps on the surface of the carbon steel electrode. Sulfate ions and hydrogen ions corrode the carbon steel surface through the gaps, thereby reducing the corrosion inhibition effect. The capacitive loop presents an imperfect semicircular arc shape, which is caused by the uneven protective film formed by RELS on the surface of Q235 steel. An inductive arc appears in the low-frequency region, which is related to the material transfer on the surface of the corrosion electrode. In the high-frequency region, a semicircular capacitive arc appears, which indicates that the corrosion of Q235 steel in acidic corrosive solutions is controlled by charge transfer resistance and double-layer capacitance. At the same RELS concentration, as the temperature increases, the capacitance arc radius gradually decreases. This is due to the increase in thermal motion of sulfate ions and hydrogen ions in the corrosive medium, indicating that high temperature is not conducive to the adsorption of RELS on the surface of Q235 steel.
[0060] Figure 2 (df) is the Bode diagram of Q235 steel without RELS and with different concentrations of RELS in 0.5 mol / L sulfuric acid medium at different temperatures (298K, 303K, 308K). It can be clearly found that with the increase of RELS concentration, the impedance modulus value diagram and the phase angle diagram show an increasing trend, and with the increase of temperature, the impedance modulus value decreases, and the phase angle diagram becomes significantly lower and narrower, which indicates that the increase in temperature is not conducive to the corrosion inhibition performance of RELS.
[0061] The Nyquist plot was fitted using Zsimpwin software, and the relevant electrochemical data were obtained in Tables 2, 3, and 4. The equivalent circuit established is shown in Figure 3 As shown, R ct is the charge transfer resistance, R sis the internal resistance, CPE represents the constant phase angle element, L and R L are inductive reactance and inductive resistance respectively. The impedance value of CPE is described by the following expression:
[0062]
[0063] Among them, Y o represents the proportional parameter, ω represents the angular frequency, which indicates the angular frequency when the imaginary part of the impedance (Zim-Max) is the maximum in the electrochemical impedance spectrum, j is the imaginary unit, n is the degree of phase shift, and CPE can be expressed as the double layer capacitance C dl The double layer capacitance formula is:
[0064] C dl =Y0(ω) n-1 =Y0(2πfZ im-Max ) n-1 (4)
[0065] Table 2. Electrochemical impedance spectroscopy parameters at 298K
[0066]
[0067] Table 3. Electrochemical impedance spectroscopy parameters at 303K
[0068]
[0069] Table 4. Electrochemical impedance spectroscopy parameters at 308K
[0070]
[0071] As shown in Table 2-4, with the increase of concentration R ct The value of shows an increasing trend, which is due to the inhibition of corrosion reaction. dl The values show a decreasing trend, which is due to the increase in the thickness of the double electric layer and the reduction of the local dielectric. As the temperature increases, the corrosion inhibition efficiency decreases. When the RELS concentration is 500 mg / L, the efficiency is 91.4% (298K), 87.28% (303K) and 83.21% (308K), which is consistent with the results of the impedance spectrum.
[0072] 2.4 Tafel curve analysis
[0073] Figure 4This is the Tafel polarization curve of Q235 carbon steel sample in 0.5mol / L sulfuric acid solution. Compared with the solution without sample addition, the current density tends to decrease with the increase of concentration. RELS can effectively reduce the corrosion of carbon steel in sulfuric acid solution. It is worth noting that the corrosion potential with the addition of RELS obviously moves toward the cathode direction, and the cathode branch decreases more significantly than the anode branch. This shows that RELS inhibits the cathode reaction more significantly
[34] In addition, the cathodic branches of the polarization curves are parallel, indicating that the addition of RELS does not change the cathode reaction mechanism.
[35] The cathode reaction and anode reaction of Q235 carbon steel in sulfuric acid solution are as follows:
[0074]
[0075] FeOH ads →FeOH + +e -
[0076]
[0077] (FeH + ) ads +e - →(FeH) ads
[0078] (FeH) ads +H + +e - →Fe+H2O
[0079]
[0080] According to the anode reaction mechanism of Q235 steel, adding RELS to the corrosive medium can form a Felnh (ads) barrier film on the surface of Q235 steel, thereby effectively inhibiting the precipitation of anode iron ions. The corrosion inhibitor replaces the adsorption of anode water molecules at the Q235 carbon steel / water solution interface, which indicates that a denser organic corrosion inhibitor protective film is formed on the surface of Q235 carbon steel.
[0081] It can be seen from Table 5-7 that at the same temperature, as the concentration of corrosion inhibitor increases, the current density gradually decreases. When the concentration of corrosion inhibitor is 500 mg / L, the corrosion inhibitor efficiency reaches the optimal level. When the concentration of corrosion inhibitor is 600 mg / L, the corrosion inhibition performance decreases. As the temperature increases, the efficiency of metal corrosion inhibitors decreases. When the concentration of RELS is 500 mg / L, the efficiency reaches 91.7% (298K), 87.31% (303K) and 82.8% (308K). This result is consistent with the electrochemical impedance spectroscopy results.
[0082] Table 5. Polarization curve parameters of Q235 steel sheet at different RELS conditions at 298K
[0083]
[0084] Table 6. Polarization curve parameters of Q235 steel sheet at 303K under different RELS conditions
[0085]
[0086] Table 7. Polarization curve parameters of Q235 steel sheet at 308K under different RELS conditions
[0087]
[0088] 2.5 Adsorption isotherms
[0089] Isotherm analysis can effectively reflect the adsorption information of corrosion inhibitor molecules on the metal surface. We used various adsorption isotherm models to fit Tafel data. 2 The Langmuir adsorption isotherm model is considered to be the most suitable model to match the experimental data of the Tafel curve. This means that the adsorption of the corrosion inhibitor molecules on the carbon steel surface conforms to the Langmuir monolayer adsorption. The c and c / θ Langmuir adsorption isotherms generate an intercept of 1 / K ads The straight line is Figure 5 As shown. The Langmuir adsorption isotherm formula is:
[0090]
[0091] Where c is the concentration of corrosion inhibitor, θ is the surface coverage, K ads is the adsorption equilibrium constant.
[0092] 2.6 Contact angle
[0093] The contact angle measurement method was used to study the wettability of the carbon steel sample surface. It is well known that the hydrophobic structure can isolate the air and prevent carbon steel from contacting corrosive media. Figure 6 As shown in the figure, in 0.5 mol / L sulfuric acid solution, the contact angles of the carbon steel sample without RELS are 70.84°(298K), 64.43°(303K), and 55.60°(308K), while the contact angles of the carbon steel sample with corrosion inhibitor added are 106.64°(298K), 93.46°(303K), and 80.79°(308K). The results show that RELS is more likely to form a hydrophobic film on the surface of the carbon steel sample, which can isolate the hydrophilic corrosive medium.
[0094] 2.7 Scanning electron microscopy
[0095] Scanning electron microscopy was used to study the surface morphology of carbon steel samples. Figure 7 As shown, the blank carbon steel sample becomes rough due to corrosion ( Figure 7 a1-c1). With the addition of RELS, the surface of carbon steel becomes significantly smoother and the corrosion degree of carbon steel samples is significantly reduced, indicating that RELS forms a protective film on the surface of carbon steel samples, which reduces the corrosion degree of carbon steel samples ( Figure 7 a2-c2). And with the increase of temperature, the roughness of carbon steel samples increases, indicating that the RELS corrosion inhibition efficiency decreases. This is consistent with the results of electrochemical experiments.
[0096] 3. Conclusion
[0097] The above research enriched the research content of green buffers. The results of electrochemical testing and surface characterization techniques are as follows:
[0098] (1) The main components of RELS are ferulic acid, sucrose and carotene.
[0099] (2) RELS, as an environmentally friendly corrosion inhibitor, significantly slowed down the corrosion of Q235 carbon steel in 0.5 mol / L sulfuric acid solution. It is a mixed corrosion inhibitor and is more effective in inhibiting cathodic corrosion. The best corrosion inhibition effect of RELS is 91.7% at a temperature of 298 K and a concentration of 500 mg / L.
[0100] (3) The adsorption of RELS on the surface of Q235 carbon steel conforms to the Langmuir adsorption isotherm equation and belongs to the adsorption of a monolayer.
[0101] The embodiments described above are only preferred specific implementation modes of the present invention, and the protection scope of the present invention is not limited thereto. Any simple changes or equivalent replacements of the technical solutions that can be obviously obtained by any technician familiar with the field within the technical scope disclosed in the present invention belong to the protection scope of the present invention.
Claims
1. A method for preparing a Ligusticum chuanxiong rhizome extract, characterized in that: The preparation method comprises the following steps: Step 1: Crush the rhizomes of Ligusticum chuanxiong and put them into an oven to dry; Step 2: adding the dried Ligusticum chuanxiong rhizome powder into a container, and adding an ethanol solution into the container, heating and refluxing for 10 hours, cooling to room temperature, and then filtering under reduced pressure to obtain an extract; Step 3: Rotate the extract to evaporate, pour the concentrated extract into a separatory funnel, add an equal amount of petroleum ether, and repeat the extraction; Step 4: Place the aqueous phase obtained by extraction in an oven for drying, add distilled water to the dried solid, place it in a centrifuge tube and repeat centrifugation, filter with a needle filter after reduced pressure, place the filtered solution in an oven for drying, and obtain RELS powder.
2. The method for preparing the Ligusticum chuanxiong rhizome extract according to claim 1, characterized in that: In step 1, the rhizome of Ligusticum chuanxiong is crushed into 500-mesh powder.
3. The method for preparing the Ligusticum chuanxiong rhizome extract according to claim 1, characterized in that: The volume fraction of the ethanol solution in step 2 is 65%-85%.
4. The method for preparing the Ligusticum chuanxiong rhizome extract according to claim 1, characterized in that: The volume fraction of the ethanol solution in step 2 is 75%.
5. The method for preparing the Ligusticum chuanxiong rhizome extract according to claim 1, characterized in that: The number of extractions in step 3 is 3 times.
6. The method for preparing the Ligusticum chuanxiong rhizome extract according to claim 1, characterized in that: In step 4, the centrifugation times are 3 times, the centrifugal speed is 1000r / min, and the centrifugal time is 3min.
7. The method for preparing the Ligusticum chuanxiong rhizome extract according to claim 1, characterized in that: The chemical components of the RELS powder obtained in step 4 include ferulic acid, sucrose and carotene.
8. Application of Ligusticum chuanxiong rhizome extract in the preparation of metal corrosion inhibitor, characterized in that: The Ligusticum chuanxiong rhizome extract is prepared by the preparation method described in any one of claims 1 to 7.
9. A metal corrosion inhibitor, characterized in that: The invention comprises a rhizome extract of Ligusticum chuanxiong, which is prepared by the preparation method described in any one of claims 1 to 7.
10. A metal corrosion inhibitor according to claim 9, characterized in that: The concentration of the Ligusticum chuanxiong rhizome extract is 500mg / L.